2009
DOI: 10.3844/ajabssp.2009.311.318
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Response of Soybean (Glycine max) to Foliar Application of Methanol Under Different Soil Moistures

Abstract: Problem statement: Many cultivated area are situated in arid zone, where crop photosynthesis and productivity has limited by drought. Thus any treatment, such as methanol, that improve plant water relation and reduce stress impacts, could be benefit. Approach: In order to investigate effects of methanol application on some physiological properties of soybean under low water stress, a factorial experiment was done at Research Field of Faculty of Agriculture and Natural Resources, Islamic Azad University-Karaj B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Effects of seed priming on germination percentage and seedling dry weight were significant (P≤0.01), but on ns, * and **: No significant and significant at p≤0.05 and p≤0.01, respectively the plant growth and grain yield due to water deficit has also been reported for millet (Kumari, 1988;Mahalakshmi and Bidinger, 1985), rice (Yao et al, 1990), chickpea (Probhakar and Safar, 1990;Singh, 1991), sorghum (Berenguuer and Faci, 2001), common bean (Adiku et al, 2001;Ghassemi-Golezani and Mardfar, 2008), soybean Paknejad et al, 2009) and faba bean (Ghassemi-Golezani et al, 2009). Pods per plant, grains per plant and grain yield per plant of soybean were significantly affected by priming (P≤0.01), but it had no significant effect on 1000 grain weight, biological yield, grain yield and harvest index (Tab.…”
Section: Resultsmentioning
confidence: 99%
“…Effects of seed priming on germination percentage and seedling dry weight were significant (P≤0.01), but on ns, * and **: No significant and significant at p≤0.05 and p≤0.01, respectively the plant growth and grain yield due to water deficit has also been reported for millet (Kumari, 1988;Mahalakshmi and Bidinger, 1985), rice (Yao et al, 1990), chickpea (Probhakar and Safar, 1990;Singh, 1991), sorghum (Berenguuer and Faci, 2001), common bean (Adiku et al, 2001;Ghassemi-Golezani and Mardfar, 2008), soybean Paknejad et al, 2009) and faba bean (Ghassemi-Golezani et al, 2009). Pods per plant, grains per plant and grain yield per plant of soybean were significantly affected by priming (P≤0.01), but it had no significant effect on 1000 grain weight, biological yield, grain yield and harvest index (Tab.…”
Section: Resultsmentioning
confidence: 99%
“…Other stress environment may also influence leaf chlorophyll content. For instance, water deficit reduced leaf chlorophyll content of fieldgrown soybean (Paknejad et al, 2009) chlorophyll degradation as a consequence of drought stress may result in photo-inhibition and photo-bleaching (Long et al, 1994). Silva et al (2007) found that drought caused a decline in sugarcane leaf chlorophyll level, but this reduction varied among genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early detection of water-deficit stress is important for irrigation management and could serve as a selection mechanism for drought tolerance. Studies on other crops have indicated that leaf RWC and/or proline content are useful indicators for early detecting plant water-deficit stress (Bates et al, 1973;Aspinall and Paleg, 1981;Ilahi and Dorffling, 1982;Levy, 1983;Claussen, 2005;Gonzalez et al, 2008;Umebese et al, 2009;Paknejad et al, 2009). Ilahi and Dorffling (1982) investigated changes in proline of four maize varieties differing in drought resistance during a prolonged water stress period and found that proline levels increased continuously during the stress period in all the four varieties, but to different amounts with higher level of proline in the drought-susceptible varieties than the drought-resistant varieties.…”
Section: Discussionmentioning
confidence: 99%
“…Water stress also results in reduction of leaf area, where the leaf growths were inhibited and the older leaves fell down (Anyia and Herzog, 2004). Reduction of expansion of young leaves and loss of older leaves caused a decreased in the LAR in the stressed plants (Paknejad et al, 2009).…”
Section: Growth Responsesmentioning
confidence: 99%